2002
DOI: 10.1053/jhep.2002.30419
|View full text |Cite
|
Sign up to set email alerts
|

S-adenosylmethionine and methylthioadenosine are antiapoptotic in cultured rat hepatocytes but proapoptotic in human hepatoma cells

Abstract: S-adenosylmethionine (AdoMet) is an essential compound in cellular transmethylation reactions and a precursor of polyamine and glutathione synthesis in the liver. In liver injury, the synthesis of AdoMet is impaired and its availability limited. AdoMet administration attenuates experimental liver damage, improves survival of alcoholic patients with cirrhosis, and prevents experimental hepatocarcinogenesis. Apoptosis contributes to different liver injuries, many of which are protected by AdoMet. The mechanism o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
113
3

Year Published

2004
2004
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 124 publications
(125 citation statements)
references
References 38 publications
9
113
3
Order By: Relevance
“…Regarding TGM2, its elevation upon MTA accumulation correlates with the restricted doxorubicin-induced apoptotic response, as also reported in other studies (71) and with NFB activation likely mediated by its kinase activity (72). In contrast with our results, there are studies reporting the proapoptotic and antiproliferative effects induced in hepatoma cells upon exposure to pharmacological concentrations of MTA (27). This apparent discrepancy might be reconciled assuming that the MTA concentration used in other investigations is much higher than the physiological/pathological levels reported in this study.…”
Section: Partial Deletion Of Mtap Increases the Sensitivity To Liversupporting
confidence: 76%
See 1 more Smart Citation
“…Regarding TGM2, its elevation upon MTA accumulation correlates with the restricted doxorubicin-induced apoptotic response, as also reported in other studies (71) and with NFB activation likely mediated by its kinase activity (72). In contrast with our results, there are studies reporting the proapoptotic and antiproliferative effects induced in hepatoma cells upon exposure to pharmacological concentrations of MTA (27). This apparent discrepancy might be reconciled assuming that the MTA concentration used in other investigations is much higher than the physiological/pathological levels reported in this study.…”
Section: Partial Deletion Of Mtap Increases the Sensitivity To Liversupporting
confidence: 76%
“…4-methylthio-2-oxobutanoic acid is finally converted into methionine, completing the methionine salvage pathway that recycles back MTA into the one carbon metabolism to promote SAMe synthesis and therefore contribute to the maintenance of the methylation capacity of the cell. Modification of MTA levels has been associated with regulation of cell proliferation (26), apoptosis (27), and inflammatory reactions (19). However, the underlying mechanisms are still only partially understood and besides other regulatory systems, it may involve the control of protein methylation reactions.…”
mentioning
confidence: 99%
“…Although SAMe protected against okadaic acid-induced apoptosis in normal hepatocytes, it induced apoptosis in liver cancer cell lines HepG2 and HuH-7 via the mitochondrial death pathway. 39 MTA also recapitulated these actions. MTA can be derived from SAMe enzymatically and non-enzymatically.…”
Section: Same Regulation Of Hepatocyte Apoptosismentioning
confidence: 66%
“…Thus, although both mutants likely affect the function of APIP in methionine salvage, we suspect that H115A is also affecting protein conformation or stability in a way that renders APIP unable to inhibit cysteineaspartic protease 9 (CASP9)-mediated cell death. Others have reported that MTA can both inhibit and increase apoptosis depending on the cell type (50,51). Published studies showing APIP inhibition through binding to APAF-1 (31) and regulation of protein phosphorylation (36) provide alternative mechanisms where APIP could regulate apoptosis independent of its role in methionine salvage.…”
Section: Resultsmentioning
confidence: 99%